Practice and procedure of Parliament: With particular reference to the Lok Sabha - Kaul, M. N.; Shakdher. S. L.; Mishra, Anoop (Ed.) (New Delhi Lok Sabha Secretariat, 2016)
Originally compiled by M.N. Kaul and S.L. Shakdher, the first edition of 'Practice and Procedure of Parliament' came out in 1968. Since then, this oft-quoted treatise has been revised five times, in 1972, 1978, 1991, 2001 and 2009, primarily to make the publication up to date with time in the background of amendments to the Constitution and existing laws, changes in the Rules of Procedure and Conduct of Business in the Lok Sabha, new precedents and conventions. With the fourth edition published in 1991, this volume has become the official publication of the Lok Sabha Secretariat. Various chapters in the volume elucidate the parliamentary practice and procedures with empirical evidences, rulings, observations and directions by the Chair. Besides the practice and procedures, the volume also throws light on aspects of functioning of the Parliament and its Committies. Since its last publication in 2009, several measures pertaining to the working of the Lok Sabha through procedural innovations have been taken for making the parliamentary business smooth and orderly enabling it to reach out to the masses. Many new conventions and practices have also been evolved in between, necessitating further revision of the publication. The comprehensively updated Seventh Revised Edition has made this most exhaustive, authentic and authoritative work even more invaluable. Over the years, the publication has been found immensely useful by the Presiding Officers, Parliamentarians, leaders of political parties, legislators, lawyers, jurists, scholars and Political Commentators. The volume is extremely popular among the Commonwealth Parliaments and also State Legislatures in India.
Keywords: Lok Sabha Secretariat; Parliament